Current limitation by transformers with high temperature superconducting windings - V. Z. Manusov; N. V. Aleksandrov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The urgency of the discussed issue is caused by the widespread use prospect of superconductivity phenomenon in power devices including transformer for losses reduction. The main aim of the study is to investigate the influence of superconducting transformers on electromagnetic transients, to define the current limiting possibility by the superconducting transformers, to reveal the features of current limitation using superconducting transformers. The methods used in the study: calculations using the software package MatLab, ATP EMTP, the use of the superconductivity theory, mathematical modeling in power. The results: the mathematical model of electromagnetic and thermal transients during short-circuit current limiting is developed; the processes of superconducting transformer transition in the normal (nonsuperconducting) state and recovery to the superconducting state after the fault current clearance is simulated; the criterion of superconducting transformer recovery in the superconducting state after fault clearance under load is defined; the possibility of short-circuit current limiting from the viewpoint of providing the required resistance is determined.